2016
DOI: 10.1136/annrheumdis-2016-eular.3823
|View full text |Cite
|
Sign up to set email alerts
|

FRI0489 Canakinumab Improves Patient Reported Outcomes in Patients with Periodic Fever Syndromes: Table 1.

Abstract: BackgroundPeriodic Fever Syndromes (PFS) are rare autoinflammatory conditions including Familial Mediterranean Fever (FMF), Hyper-IgD Syndrome/ Mevalonate Kinase Deficiency (HIDS/MKD), and TNF-Receptor Associated Periodic Syndrome (TRAPS).1 It has been shown that colchicine-resistant FMF (crFMF), HIDS/MKD and TRAPS considerably impact physical and emotional aspects of patients' lives.2–4 Open label studies suggested that canakinumab (CAN), a fully human and highly specific anti-IL-1β monoclonal antibody, is ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…19 The HRQoL assessments revealed that canakinumab treatment led to early clinically meaningful improvements in SF-12 Physical Component Summary (PCS), CHQ-PF50 Physical Subscale (PhS) and CHQ-PF50 Psychosocial Subscale (PsS) scores at week 5, which were sustained and increased to a large effect size by week 16. 20 In an open-label, 3-part non-RCT, all HIDS/MKD patients achieved a CR with canakinumab during 6-month treatment period. 26 Disease relapsed in 78% of patients during the canakinumab withdrawal period.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…19 The HRQoL assessments revealed that canakinumab treatment led to early clinically meaningful improvements in SF-12 Physical Component Summary (PCS), CHQ-PF50 Physical Subscale (PhS) and CHQ-PF50 Psychosocial Subscale (PsS) scores at week 5, which were sustained and increased to a large effect size by week 16. 20 In an open-label, 3-part non-RCT, all HIDS/MKD patients achieved a CR with canakinumab during 6-month treatment period. 26 Disease relapsed in 78% of patients during the canakinumab withdrawal period.…”
Section: Resultsmentioning
confidence: 99%
“…19 In HRQoL assessments, canakinumab provided early clinically meaningful improvements in SF-12 PCS, CHQ-PF50 PhS and CHQ-PF50 PsS scores at week 5, which were sustained and increased in magnitude by week 16. 20 In the Phase II non-RCT, 19/20 patients (95%) with active recurrent/chronic TRAPS achieved a CR with canakinumab. 27 Disease relapsed in all patients during canakinumab withdrawal period, but similar responses were attained and sustained on retreatment with canakinumab.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…По мнению авторов, результаты исследования доказывают патогенную роль ИЛ1β при этих заболеваниях. И у взрослых, и у детей отмечалось су-щественное улучшение показателей, отражающих физи-ческий и ментальный компонент качества жизни [44]. Эффективность, хорошая переносимость терапии инги-биторами ИЛ1, в частности канакинумабом, наблюдались также у пациентов с FMF, перенесших трансплантацию донорской почки [45].…”
Section: криопирин-ассоциированные периодические синдромыunclassified